Reinduction of hedgehog inhibitors after checkpoint inhibition in advanced basal cell carcinoma: a series of 12 patients - DeTemple, Viola; Hassel, Jessica C.; Sachse, Michael M.; Grimmelmann, Imke; Leiter, Ulrike; Gebhardt, Christoffer; Eckardt, Julia; Pföhler, Claudia; Angela, Yenny; Hübbe, Hanna; Gutzmer, Ralf (Cancers, 2022)
For patients with advanced basal cell carcinoma (aBCC) first-line treatment with hedgehog inhibitors (HHIs) and second-line treatment with PD1 inhibitors (PD1i) is available, offering combination and sequencing options. Here, we focus on the efficacy and safety of HHI reinduction after PD1i failure.